Reduction of Parkinsonism and Psychosis with Mirtazapine: A Case Report - Godschalx-Dekker, J. A.; Siegers, H. P. (Pharmacopsychiatry, 2014)
Introduction: Psychosis in Parkinson disease is a therapeutic challenge. Regular strategies of treatment are aimed at reducing dopamine medication, and if necessary addition of clozapine.Methods: We describe the case of a patient with persistent psychosis. Nocturnal visual hallucinations persisted in spite of reduced dopaminergic medication and sequential treatment with atypical antipsychotic medication (quetiapine and clozapine) in combination with an acetylcholinesterase inhibitor (rivastigmine). After dispensing a dopamine enhancing antidepressant (mirtazapine), prescribed to improve sleeping, the psychotic symptoms almost immediately disappeared while Parkinsons symptoms declined.Results: One other case about a positive effect of mirtazapine on (auditory) hallucinations in Parkinson has been published. The reason for the reduction of psychosis in Parkinson-related disease could have been the effect of antagonism of serotonin (5HT)-2 A and/or antagonism of 5HT-2C leading to dopamine release.Discussion: Therapeutic effects of medication with strong antagonism for 5HT-2 A and 5HT-2C, like mirtazapine, mianserine, trazodone and nefazodone, in Parkinson-related diseases should be subject for further research. Serotonin might be associated with psychosis in Parkinson-related disease.
Keywords: psychosis; hallucinations; mirtazapine; SSRI; Parkinson’s disease; Lewy bodies